2017
DOI: 10.17113/ftb.55.02.17.4883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Solasonine Content and Expression Patterns of SGT1 Gene in Different Tissues of Two Iranian Eggplant (Solanum melongena L.) Genotypes

Abstract: The family of Solanaceae (also known as nightshade family) is considered as a large plant family including essential crops such as potato, tomato, sweet pepper and lastly eggplant (1). In both tropical and temperate regions of the world, eggplant (Solanum melongena L., 2n=2x=24) has been cultivated for years, and regarded currently as an economically important vegetable plant (2). Phylogenetically, contrary to the other important Solanaceae fam- SummaryEggplant (Solanum melongena L.) is one of the most consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Researchers showed that SGAs have an antiparasitic effect on Leishmania mexicana (Lezama-Dávila et al, 2016), Leishmania amazonensis (Miranda et al, 2013) and Trypanosoma cruzi (Hall, Hobby & Cipollini, 2006;Chataing, Concepción, Lobatón, & Usubillaga, 1998). Although they have beneficial effects, glycoalkaloids are toxic to humans and can even cause death at high concentrations (3-5 mg/kg body mass) (Bagheri, Bushehri, Hassandokht & Naghavi, 2017). Market eggplant, S. melongena, has lower levels of glycoalkaloids than the toxic dose (Table S3).…”
Section: Glycoalkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers showed that SGAs have an antiparasitic effect on Leishmania mexicana (Lezama-Dávila et al, 2016), Leishmania amazonensis (Miranda et al, 2013) and Trypanosoma cruzi (Hall, Hobby & Cipollini, 2006;Chataing, Concepción, Lobatón, & Usubillaga, 1998). Although they have beneficial effects, glycoalkaloids are toxic to humans and can even cause death at high concentrations (3-5 mg/kg body mass) (Bagheri, Bushehri, Hassandokht & Naghavi, 2017). Market eggplant, S. melongena, has lower levels of glycoalkaloids than the toxic dose (Table S3).…”
Section: Glycoalkaloidsmentioning
confidence: 99%
“…Glycoalkaloids are found at different concentrations in different parts of the plants and at different developmental stages as is the case with different wild relatives and varieties of eggplant. The highest solasodine content was observed in flower buds, followed by leaf, physiologically ripe fruit, young fruit, and mature fruit (Bagheri et al, 2017). It is well known that glycoalkaloids are effective inhibitors of cancer cells due to their toxic effects.…”
Section: Glycoalkaloidsmentioning
confidence: 99%
“…Bagheri et al. () compared two different aubergine genotypes, of which one (D1) had ‘sweet’ fruits and the other (J10) had ‘bitter’ fruits, with regard to the content of α‐solasonine (α‐solamargine was not analysed in this study) as well as concerning the expression of SGT1 in the leaves, flower buds, young fruits, mature fruits and physiologically ripe fruits. The levels of α‐solasonine closely followed the expression of the SGT1 gene in the same plant tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In all tissues, the concentration of α‐solasonine in the bitter variety was between two and three times higher than in the sweet variety. Concentrations of α‐solasonine reported for the D1 and J10 genotypes, respectively, were leaves: 113.3 and 249.3 mg/kg dw; flower buds: 135.6 and 478.8 mg/kg dw; young fruits: 61.3 and 160.4 mg/kg dw; mature fruits: 21.6 and 45.6 mg/kg dw and physiologically ripe fruits: 74.7 and 185.0 mg/kg dw (Bagheri et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, literature has shown that the SGAs have an antiparasitic effect on Trypanosoma cruzi , Leishmania amazonensis, and Leishmania mexicana [ 21 ]. Though glycoalkaloids have beneficial effects as inhibitors of cancer cells, they are also toxic to humans and can cause death if injected in higher concentrations at 3 to 5 mg/kg body mass [ 25 ]. Therefore, the optimal levels for toxicity should be further studied.…”
Section: Economic Importance Of Eggplantmentioning
confidence: 99%